The reason for the weakness of many learners in the Arabic language subgect is the dryness,difficuity,and stagnation of the subgect Arabic. (Journal of the College of Basic Education, 2024)
The success of learning is largely linked to the success of the model,and the model,which is one of the modern methods that addresse the the weakness ofcurriculum,the weakness of the learner,and the difficulty of thetext book,can there fore be determined.Research problem with guestion:What is the effect of the koscroffs on the acquisition of Araic grammar among primary grade female students .The researcher explains the importance of research,the importance of education as the most extensive field,the importance of grammar in the Arabic language is not written correctly except by knowing its basic rules,and the importance of methods of writing.New ideas, prior knowledge, and the importance of the preparatory stage that excites the learner to search for knowledge.The researcher conducted statistical eguivalence in the chronological age calculated in months and using the t-test abd found that there was no statistically significally significant difference between the average ages of the two research groups at a significance level of(0.5)and a degree of freedom(f).it becomes clear that the difference isn't stati stically significant at a sign ificance le vel or is less than the value.T(permanence of the- calculated Tvalue)(2,000 )tabular.The researcher found that there is no difference and statistical significance between the average scores of the female students of the two research groupsat the level of singnificance(0.5) and the degree of freedom(6).The research community is represented by female students in the fifth literary grade in one of the schools in the Education Directorate Governorate the first order is if the sample size is(35)according to the methods used,which is the t-test for my sample.